Critical role of factors II and X during coumarin anticoagulation and their combined measurement with a new Fiix-prothrombin time - Gudmundsdottir, Brynja R.; Francis, Charles W.; Bjornsdottir, Alexia M.; Nellbring, Moa; Onundarson, Pall T. (Thrombosis research, 2012)
Vitamin K antagonists (VKA) are monitored with prothrombin time (PT) based assays that are equally sensitive to reductions in factors II, VII or X. We compared the effect of vitamin K dependent (VKD) coagulation factors on PT and also on rotational thromboelastometric (ROTEM) parameters. The PT was equally sensitive to reductions in factors II, VII or X but ROTEM parameters correlated poorly with the PT in anticoagulated patients´ plasmas. ROTEM parameters were more affected by mild and moderate reductions in FII or FX than by FVII or FIX which had little influence except at very low coagulant activity. We developed a modified PT that was sensitive only to reductions in factors II and X. The Fiix-PT (Fiix-INR) correlated well with PT (INR) but the Fiix-INR fluctuated less than the INR in an anticoagulated patient reflecting its insensitivity to FVII. The ROTEM results suggest that mild to moderate reductions in factors II or X are more important during clot formation than factors VII or IX. Reductions in FII and X may better reflect anticoagulation with VKA than FVII or IX. The new Fiix-PT may more accurately reflect the degree of therapeutic anticoagulation in patients treated with VKA than the current PT which is subject to a confounding variation caused by FVII.